Isolat bakteri asam laktat untuk mengendalikan Aeromonas hydrophila pada ikan nila (Oreochromis niloticus): Isolates of lactic acid bacteria to control Aeromonas hydrophila in tilapia (Oreochromis niloticus) - Sundari Hidayat; Gina Saptiani; Agustina (Jurnal Ilmu Perikanan Tropis Nusantara (Nusantara Tropical Fisheries Science Journal), 2023)
Tilapia is one type of freshwater fish that has high economic value. With the increasing demand by the community, tilapia is cultivated in a semi-intensive system so that bacterial diseases caused by Aeromonas hydrophila arise. One way to treat disease in fish safely is the use of lactic acid bacteria. The purpose of this study was to examine the isolates of lactic acid bacteria in controlling diseases caused by Aeromonas hydrophila in tilapia. This study used a completely randomized design experimental method with 4 treatments and 3 replications. The treatments consisted of feed mixed with Phosphate Buffered Saline (PBS), Enterococcus faecalis isolate, Lactobacillus plantarum isolate and Lactococcus lactis isolate at a dose of 0.1 mL/g of feed at a concentration of 106 CFU/mL and mixed with 0.1 mL of egg white. The results showed that the treatment with lactic acid bacteria affected the condition of clinical symptoms and anatomical pathology of tilapia, but was better than the control treatment. The feed mixed with lactic acid bacteria also had an effect on increasing the immune response and showed higher survival than the control treatment. The condition of water quality in the rearing media showed the normal range for the life of tilapia.